Analysing the State of the Information Society in Ukraine - Kozlov, V. V.; Tomashevska, T. V.; Dyvak, V. V. (Statistics of Ukraine, 2024)
The digital divide, or the divide between the ones who have access to technologies and can effectively use them, and the ones who does not have them, has been in focus of the overwhelming majority of research addressing information society issues. Research into the access of counties’ populations to advanced technologies shows that in spite of the rapid dissemination of mobile communication and Internet in developing counties, the global digital divide has been increasing. The broadband rapid connection to Internet has opened up opportunities of prosperity for certain population groups by helping them receive technological know-how required for gaining success in the digital economy. Entities with access to technologies enjoy more opportunities than ever before. But the regions with limited population’s access to digital technologies see essentially worsened conditions for improvements of living standards, thus shrinking capabilities for development. This situation is not favorable for the information society building, because it reduces the overall potential of a region or a country for gaining benefits from utilization of advanced technologies, resulting in deeper social and economic crises. Apart from the familiarity with a wide spectrum of technological tools, future success of a country requires their practical command. If a country strives for technological development and sustained global competitiveness, its residents need to have a high level of technological competence. The challenge of digital divide still remains acute for Ukraine. The article discusses issues of determining the factors with impact on access to information and communication technologies (ICT) and ICT command across Ukrainian regions. A factor analysis helped author distinguish between two broad factors, with the first one associated with financial support to the ICT development in a region, and the second one relating to the expansion of the segment of residents with good ICT command. An analysis of the regions grouped by these factors showed that the majority of Ukrainian regions had poor funding for ICT implementation, which, in turn, is a principal cause for the digital divide in Ukraine.